Association of the combined effects of air pollution and changes in physical activity with cardiovascular disease in young adults. (1st April 2021) - Kim, Seong Rae; Choi, Seulggie; Kim, Kyuwoong; Chang, Jooyoung; Kim, Sung Min; Cho, Yoosun; Oh, Yun Hwan; Lee, Gyeongsil; Son, Joung Sik; Kim, Kyae Hyung; Park, Sang Min
Abstract: Aims: Little is known about the trade-off between the health benefits of physical activity (PA) and the potential harmful effects of increased exposure to air pollution during outdoor PA. We examined the association of the combined effects of air pollution and changes in PA with cardiovascular disease (CVD) in young adults. Methods and results: This nationwide cohort study included 1 469 972 young adults aged 20–39 years. Air pollution exposure was estimated by the annual average cumulative level of particulate matter (PM). PA was calculated as minutes of metabolic equivalent tasks per week (MET-min/week) based on two consecutive health examinations from 2009 to 2012. Compared with the participants exposed to low-to-moderate levels of PM2.5 or PM10 who continuously engaged in ≥1000 MET-min/week of PA, those who decreased their PA from ≥1000 MET-min/week to 1–499 MET-min/week [PM10 adjusted hazard ratio (aHR) 1.22; 95% confidence interval (CI) 1.00–1.48] and to 0 MET-min/week (physically inactive; PM10 aHR 1.38; 95% CI 1.07–1.78) had an increased risk of CVD ( P for trend <0.01). Among participants exposed to high levels of PM2.5 or PM10, the risk of CVD was elevated with an increase in PA above 1000 MET-min/week. Conclusion: Reducing PA may lead to subsequent elevation of CVD risk in young adults exposed to low-to-moderate levels of PM2.5 or PM10, whereas a large increase in PA in a high-pollution environment may adversely affect cardiovascular health. Graphical Abstract: